Cooperative Learning Model of Time Based Learning Type Assisted by Media Box: Elementary School Students' IPAS Learning Outcomes - Parida, Parida; Irviana, Ira; Afni, Nur (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The background of the research is the low academic achievement of students; only 37.03% of 27 students achieved the minimum completion criteria in the preliminary study. Therefore, this study examines the application of a time-based learning-type cooperative learning model assisted by media boxes to improve the learning outcomes of social studies/IPAS of elementary school. This study uses classroom action research with the Kemmis and McTaggart model research design. This research was conducted with grade V students at 108 Moncongloe Home Base. This research used observation, tests, and documentation instruments. The results of the analysis showed a significant increase in student learning outcomes after applying the model using media boxes. This can be seen in the increase in the average score of student learning outcomes from cycle I, which is 56.14%, to cycle II, which is 77.62%. Thus, a time-based learning-type cooperative learning model assisted by media boxes can improve student learning outcomes.